2004
DOI: 10.1023/b:mcbi.0000028737.94213.2f
|View full text |Cite
|
Sign up to set email alerts
|

Orally administered tryptophan and experimental type 2 diabetes

Abstract: There is a link between diabetes and oxidative stress. Hyperglycaemia leads to free radical generation and alterations of endogenous antioxidants. Our aim is to study the effect of orally administered L-tryptophan (TRP), the melatonin precursor, an endogenous antioxidant, on circulating levels of glycaemia, insulin and melatonin, and on the superoxide dismutase and catalase antioxidant systems in non-diabetic (ND) and type 2 diabetic (n5-STZ) male Wistar rats. At 19:30 every day for 15 days, TRP (125 mg/kg bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
3
14
1
Order By: Relevance
“…With respect to SOD, the enzyme responsible for neutralizing superoxide anion levels, this study showed no changes in SOD activity in the n5-STZ rats. These results corroborate with literature, which observed no significant changes in SOD activity in diabetic rats 36,37 . However, there are also conflicting findings in literature.…”
Section: Discussionsupporting
confidence: 93%
“…With respect to SOD, the enzyme responsible for neutralizing superoxide anion levels, this study showed no changes in SOD activity in the n5-STZ rats. These results corroborate with literature, which observed no significant changes in SOD activity in diabetic rats 36,37 . However, there are also conflicting findings in literature.…”
Section: Discussionsupporting
confidence: 93%
“…It was observed from this study that the daonil supplemented tryptophan resulted in minimal change in both the weight and glucose concentration, but daonil only had significant reduction on the weight and glucose concentration, this was more noticeable on the 7 th day. The oral administration of tryptophan did not change the glycaemia level this was also observed in the course of this study [31]. The results obtained from other investigation suggested that tryptophan suppresses the elevation of blood glucose and lessens the burden associated with insulin secretion from β-cells, this agrees with our findings in which there was a decrease in glucose level on day 7 th in the group treated with tryptophan only.…”
Section: Recommendationsupporting
confidence: 93%
“…The OGTT was performed after 16-h fasting in SD or SDT rats with glucose (2 g/kg body weight (BW)), plus either l-or d-tryptophan (62.5 mg/kg BW) (12). Blood samples were collected from the inferior vena cava at the indicated times after oral administration of glucose.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of l-tryptophan on blood glucose level have been complex, because not only l-tryptophan itself upregulates gluconeogenesis in liver (8), but also its metabolites including 5-hydroxy-tryptamine and serotonin (5-HT) modulate insulin secretion (9) and glucose uptake into skeletal muscle (10), as well as melatonin-stimulated insulin secretion (11). Recently, it was reported that oral administration of l-tryptophan for 15 d did not modify glycermia or insulinemia, but raised melatonin in T2DM model rats (12).…”
mentioning
confidence: 99%